Taubat Dalam Perspektif Al-Qur’an - Rinalpi Rinalpi; Inong Satriadi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The main problem in this thesis is repentance in the perspective of the Qur'an (study of thematic interpretation). As for the purpose of this study based on the formulation of the problem above, namely To describe and analyze how the Qur'an views the commands of repentance, the reward for repentance, the conditions for receiving repentance, and the causes for repentance. Thematic or maudhu'i interpretation and analysis methods are used in this type of library research. Data processing is done by clarifying verses about repentance from the perspective of the Qur'an, studying thematic interpretations, then processing and exploring the interpretation by referring to the book of Tafsir Muyassar and presenting it in effective sentences. The results of research related to repentance are fourfold: first, the command to repent is in the plural form, which means that it must be done by all humans and the law becomes mandatory. Second, there are seven replies to repentance. Third, the conditions for acceptance of repentance are seven and must be met. Fourth, there are nine reasons why a person repents.